Paramecium jenningsi complex: existence of three cryptic species confirmed by multi-locus analysis and strain crosses. Issue 2 (3rd March 2016) - Przyboś, Ewa; Tarcz, Sebastian
Abstract : Ciliates (Protista) have a complex species structure, which means that in several genera the morphological species are differentiated into cryptic species with isolated gene pools (called syngens). Problems of speciation are well known in the genus Paramecium, and especially in the P. aurelia sibling (cryptic) species complex within it. However, the problem of the existence of such species within P. jenningsi was, until recently, still unsolved. Here we present the results of studies based on an analysis of 16 loci (both nuclear and mitochondrial), strain crosses and cytological preparations. The obtained data allowed us not only to study relationships of the P. jenningsi complex and other morphospecies within the Paramecium subgenus, but also to confirm the existence of three isolated reproductive groups within the former P. jenningsi and to propose binominal names for each of them: P. primjenningsi, P . bijenningsi, and P. trijenningsi . In our view, the studied species meet the criteria of a species complex because they can be differentiated based on strain crosses and molecular characteristics, but they cannot be differentiated based on morphological features alone. http://zoobank.org/urn:lsid:zoobank.org:pub:9209CD4C-A255-4A33-BFC1-CE336244C200